Trade relations between Peru and Japan: the need for change - Castellanos, Enrique (1989)
International Trade of Goods has been the main economic link between Peru and the rest of the world. However, in the present decade, Peruvian international trade faces a severe crisis, wicha has driven to a deep fall of the export and import quantum. In this view, the present article tries to point out the huge potential in terms of export that in the present represents on Japan for Peru. In the first part, there is a short diagnosis for the nature and crisis of Peruvian-Japanese trade. Secondly, the authors state the main tools of an appropiate pro-exporting commercial policy for Peru. Finally, we try to depict a strategy for penetrating the Japanese market.